An interactive algorithm for multiple criteria constrained sorting problem - Özpeynirci, Selin; Özpeynirci, Özgür; Mousseau, Vincent (Annals of operations research, 2018)
In this study, we consider the multiple criteria constrained sorting problem and propose an interactive algorithm. The problem is to assign alternatives evaluated on multiple criteria to sorted categories where categories may have size restrictions. The proposed interactive algorithm determines the eligible categories for each alternative and the alternatives with a single eligible category are assigned to the corresponding categories. In case of no such alternative exists, the algorithm asks the DM to assign an alternative to a category and proceeds. The algorithm has the capability to detect and resolve any inconsistencies that may arise during the iterations. We implement the algorithm on two different real life problems considering two underlying sorting methods, MR-Sort and UTADIS and present the computational results.